Korean art collection : Victoria and Albert Museum - Kim, Yŏng-wŏn, 1953-; National Research Institute of Cultural Heritage (Daejeon : National Research Institute of Cultural Heritage, 2013)
Overzicht van de Koreaanse kunst die in het bezit is van het Victoria en Albert Museum: voornamelijk aardewerk.
In Korean and English, with catalog captions also in Chinese and abstract in Japanese and Chinese.